Short-term leaching of heavy metals from cement from co-processing of industrial sludge containing petroleum and heavy metals as an alternative fuel - Nuntira Supasai (Chulalongkorn University, 2014)
Thesis (M.Sc.)--Chulalongkorn University, 2007